The Role of Helicobacter Pylori Proinflammatory Outer Membrane Protein and Propolis in Immunomodulation on U937 Macrophage Cell Model: - Falsafi, Tahereh; Soudi, Hengameh; Gharavi, Sara (Galen Medical Journal, 2020)
Background: Regarding the important role of proinflammatory outer membrane protein (OipA) in the pathogenesis of Helicobacter pylori infection and immunomodulatory activity of propolis, we aimed to evaluate the immunogenicity effect of a purified recombinant OipA protein and propolis in the induction of two cytokines, interferon-gamma (IFN-γ) and interleukin-4 (IL-4), in a macrophage cell model. Materials and Methods: The recombinant protein used in the present study corresponding to the oipA expressing a 34-35 kDa protein. OipA protein was purified by Ni-NTA affinity chromatography. The purified OipA protein (2.5- 40 μg /mL) and the propolis ethanolic extract (5-40 μg/mL) were incubated with phorbol 12-myristate 13-acetate-treated human myelomonocytic cell line U937 cells. IL-4 and IFN-γ levels were measured after 48 hours of incubation using enzyme-linked immunosorbent assay. Results: The amounts of IL-4 and IFN-γ were significantly increased. The optimum concentration of OipA for the secretion of IL-4 was 5 μg/ml (P<0.0001). At higher concentrations, the amount of IL-4 diminished until suppression at 40 μg/mL. The optimum concentration of propolis, resulting in the most significant increased secretion of both IL-4 and IFN-γ was 40 μg/mL (P=0.0001 and P=0.0004). Conclusion: We found that an OipA concentration of 10 μg/mL was more effective for IFN-γ production; however, it was not effective for the high production of IL-4. Therefore, it is postulated that the OipA could mainly induce a Th1 response through the production of IFN-γ. We also observed propolis’s capability to induce IFN-γ production; however, the effective concentration for this was the same as for IL-4. Therefore, as an adjuvant, proper concentration of propolis is required for OipA to give the optimum response. [GMJ.2020;9:e1687]